Founder Effects of Spinocerebellar Ataxias in the American Continents and the Caribbean - Rodríguez-Labrada, Roberto; Martins, Ana Carolina; Magaña, Jonathan J.; Vazquez-Mojena, Yaimeé; Medrano-Montero, Jacqueline; Fernandez-Ruíz, Juan; Cisneros, Bulmaro; Teive, Helio; McFarland, Karen N.; Saraiva-Pereira, Maria Luiza; Cerecedo-Zapata, César M.; Gomez, Christopher M.; et al. (Cerebellum (London, England), 2020)
Spinocerebellar ataxias (SCAs) comprise a heterogeneous group of autosomal dominant disorders. The relative frequency of the different SCA subtypes varies broadly among different geographical and ethnic groups as result of genetic drifts. This review aims to provide an update regarding SCA founders in the American continents and the Caribbean as well as to discuss characteristics of these populations. Clusters of SCAs were detected in Eastern regions of Cuba for SCA2, in South Brazil for SCA3/MJD, and in Southeast regions of Mexico for SCA7. Prevalence rates were obtained and reached 154 (municipality of Báguano, Cuba), 166 (General Câmara, Brazil), and 423 (Tlaltetela, Mexico) patients/100,000 for SCA2, SCA3/MJD, and SCA7, respectively. In contrast, the scattered families with spinocerebellar ataxia type 10 (SCA10) reported all over North and South Americas have been associated to a common Native American ancestry that may have risen in East Asia and migrated to Americas 10,000 to 20,000 years ago. The comprehensive review showed that for each of these SCAs corresponded at least the development of one study group with a large production of scientific evidence often generalizable to all carriers of these conditions. Clusters of SCA populations in the American continents and the Caribbean provide unusual opportunity to gain insights into clinical and genetic characteristics of these disorders. Furthermore, the presence of large populations of patients living close to study centers can favor the development of meaningful clinical trials, which will impact on therapies and on quality of life of SCA carriers worldwide.